CONODONT BIOSTRATIGRAPHIC FRAMEWORK FOR NORTHERN KEDAH, PERLIS AND LANGKAWI ISLANDS, PENINSULAR MALAYSIA - BASHARDIN, ATILIA (2014)
This study has tested and validated the suggestion of Cocks et al. (2005), that the Langkawi Islands, mainland Kedah, Perlis and southern Thailand had been deposited in the same basin which is part of the Sibumasu Terrane. This study aims to provide palaeotemperatures and more comprehensive conodont biostratigraphical correlations for the Western Belt of Peninsular Malaysia.